Domain evolution processes in ferroelectric ceramics - Kim, K (2015)
The aim of this doctoral research is to understand domain evolution processes in ferroelectrics using piezoresponse force microscopy (PFM) and Monte Carlo simulation. The results provide improved knowledge of domain evolution processes, and systematic experimental methods for research on domain evolution. There has been extensive previous research on domain evolution in ferroelectrics, but the research was mainly constrained to simple domain patterns. However, ferroelectric domains tend to form complex patterns that generate low-energy domain configurations. In this research, several methods such as statistical analysis of PFM data, ex situ/in situ PFM observation under electrical/mechanical loading and combining PFM with electron backscatter diffraction are employed to study domain evolution processes in complex domain patterns. The results show that domain switching almost always takes place by the evolution of pre-existing domain patterns, rather than direct flipping of polarization. Also the net effect of domain evolution processes follows a primary principle that positive work is done by external loads. But this principle is not always followed for microscopic switching processes. Multiple types of domain switching occur simultaneously, and occasionally an overwriting process involves unfavourable as well as favourable domain switching. Domain switching is significantly constrained by the pre-existing domain patterns. Meanwhile, angle-resolved PFM is developed for the systematic interpretation of PFM signal. Using lateral PFM images taken from multiple sample orientations, angle-resolved PFM maps are generated based on the angle of phase reversal in the PFM signal. The resulting maps reliably show complex domain patterns which may not appear in vertical and lateral PFM images. A model of domain evolution is developed using Monte Carlo simulation. Polarization switching by electric field and mechanical stress in the model is shown to take place via the motion of domain walls between pre-existing domains. Typical domain broadening processes are reproduced through this simulation.